Oblique Lateral Interbody Fusion vs. Minimally Invasive Transforaminal Lumbar Interbody Fusion for Lumbar Spinal Stenosis: A Retrospective Cohort Study - Gao, Quan-You; Wei, Fei-Long; Li, Tian; Zhu, Kai-Long; Du, Ming-Rui; Heng, Wei; Yang, Fan; Gao, Hao-Ran; Qian, Ji-Xian; Zhou, Cheng-Pei (Frontiers in Medicine, 2022)
Background Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) is an effective surgical option for lumbar spinal stenosis (LSS) with spondylolisthesis. However, few studies have discussed oblique lateral interbody fusion (OLIF) with MIS-TLIF. Objective To evaluate postoperative improvements, complications, and reoperation rates between patients with LSS undergoing OLIF or MIS-TLIF. Methods We retrospectively studied 113 LLS patients who underwent OLIF (53) or MIS-TLIF (60) with percutaneous pedicle screw fixation between January 2016 and December 2018. We measured estimated blood loss, operative time, hospital stay, reoperation, and complication incidence, visual analog scale (VAS), Oswestry Disability Index (ODI), Japanese Orthopedic Association (JOA), and Short Form-36 (SF-36) scores, discal and foraminal height and lumbar lordotic angle. Results The mean age was 58.81 ± 0.9 years. The TLIF group had increased operation time, blood loss, and hospital stays (p = 0.007, 0.001, and 0.016, respectively). Postoperatively, VAS and ODI scores significantly decreased while JOA and SF-36 scores significantly increased. The postoperative differences in main outcomes between the groups were insignificant (all p > 0.05). The OLIF group had the lowest rates of overall (9.8% OLIF vs. 12.9% MIS-TLIF), intraoperative (3.9% OLIF vs. 4.8% MIS-TLIF), and postoperative complications (5.9% OLIF vs. 8.1% MIS-TLIF), but the differences were insignificant (p = 0.607, 0.813, and 0.653, respectively). The reoperation rate did not differ significantly (3.8% OLIF vs. 3.3% MIS-TLIF) (p = 0.842). OLIF restored disc height (74.4 vs. 32.0%), foraminal height (27.4 vs. 18.2%), and lumbar lordotic angle (3.5 vs. 1.1%) with greater success than did MIS-TLIF. Conclusion Patients undergoing OLIF with LSS improved similarly to MIS-TLIF patients. OLIF restored disc height, foraminal height and lumbar lordotic angle more successfully than did MIS-TLIF.